2011
DOI: 10.1517/14712598.2011.585153
|View full text |Cite
|
Sign up to set email alerts
|

Fetal gene therapy: recent advances and current challenges

Abstract: Although there are valid safety and ethical concerns, the authors argue that there may soon be enough convincing evidence from non-human primate models to take the next step towards clinical trials in the near future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 121 publications
0
12
0
Order By: Relevance
“…We have recently demonstrated that global nervous system transduction can be achieved after in utero intravenous administration of this vector in fetal mice and late‐gestation NHPs (8, 9). Considering the potential benefits of fetal therapy from the perspectives of the recipient and the burden on vector production, perinatal gene delivery is a suitable strategy for treating diseases when irreversible pathology begins in utero or at birth and for conditions affecting growth and development (10).…”
mentioning
confidence: 99%
“…We have recently demonstrated that global nervous system transduction can be achieved after in utero intravenous administration of this vector in fetal mice and late‐gestation NHPs (8, 9). Considering the potential benefits of fetal therapy from the perspectives of the recipient and the burden on vector production, perinatal gene delivery is a suitable strategy for treating diseases when irreversible pathology begins in utero or at birth and for conditions affecting growth and development (10).…”
mentioning
confidence: 99%
“…Multiple outstanding reviews have been written over the last decade, discussing IUGT in detail. 2 , 16 , 25 , 89 , 147–155 For this reason, we will endeavor to highlight some of the key advantages and risks to this, as yet, experimental therapeutic approach, focusing on the utility of this treatment modality for correcting hemophilia A (HA). It is important to note that many genetic diseases exert a significant amount of irreversible damage during embryonic and fetal development.…”
Section: Iugt: Rationale For Approachmentioning
confidence: 99%
“…Fetal gene therapy is inherently flawed as the potential detrimental phenotypic effects of any genetic mutation, be it at the chromosomal or molecular level, have already occurred in the embryonic period. Albeit with some minor success, in utero treatment has been applied to fetuses at risk for a number of genetic and congenital anomalies, including congenital diaphragmatic hernia, cystadenomatoid malformation of the lung and saccrococygeal teratoma, shunts for uropathies and thoracic fluids, pharmacological therapies for congenital adrenal hyperplasia and neural tube defect as well as stem cell treatment of severe combined immunodeficiency disorder [ 26 , 27 , 28 , 29 , 30 ]. The insights gained over the past decade with regard to stem cell biology as well as the ability to manipulate genetic sequences are two of an increasing number of technologies whereby there now are opportunities to alter the course of abnormal development during the critical time of embryogenesis, as summarized next.…”
Section: Introductionmentioning
confidence: 99%
“…This will be an especially arduous scientific journey, requiring novel technologies involving embryonic visualization [ 37 ], gene manipulations [ 33 ] and/or transplantation of genetically-altered mesenchymal stem cells [ 27 ], all with the goal to ameliorate potential physical and functional damage. It is anticipated that the first effective therapies would be applied to a collective group of monogenic disorders for the purpose of achieving phenotypic cure early in the disease process and before the development of permanent organ damage [ 29 ].…”
Section: Introductionmentioning
confidence: 99%